Hubungan Umat dan Pemerintah: Studi Hermeneutik terhadap Roma 13:1-7 - Otniel Aurelius Nole (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2023)
The people and the government are the two main figures in the order of life. The government has important roles and works with devotion. The presence of the people helps the government. The people have obligations to respect the government, but sometimes there are neglects to obey the government. In the Bible, Paul's letter Romans 13:1-7 states about the relationship between people and government. The social situation describes the presence of the people and the government. Paul emphasized the importance of the people to obey the government. This paper aims to investigate the relationship between the people and the government and find their relevance in the Indonesian context. This paper is reviewed with a hermeneutic study of Romans 13:1-7. The author explores the socio-historical context relating to Rome and the Roman Empire. The research method used is qualitative with a hermeneutic study based on critical approaches. The result found is that God is sovereign over the people and the government. Then, the people and the government have a relationship of mutualism and interdependence. Both work together in the order of life. The government is God's messenger who is given the task of protecting and helping the people. The people pay respect to the government as God's servants.Umat dan pemerintah adalah dua figur utama yang berada dalam tatanan kehidupan. Pemerintah berperan penting dan bekerja dengan pengabdian. Kehadiran umat turut membantu pemerintah. Umat memiliki kewajiban untuk menghormati pemerintah, tetapi terkadang terjadi kelalaian untuk mematuhi pemerintah. Di dalam Alkitab, surat Paulus di  Roma 13:1-7 menyatakan tentang keterkaitan antara umat dan pemerintah. Keadaan sosialnya menggambarkan kehadiran umat dan pemerintah. Paulus menegaskan kepentingan untuk umat patuh kepada pemerintah. Tulisan ini bertujuan untuk menginvestigasi hubungan umat dan pemerintah, serta menemukan relevansinya dalam konteks Indonesia. Tulisan ini ditinjau dengan studi hermeneutik terhadap Roma 13:1-7. Penafsir mengeksplorasi konteks sosio-historis yang berkaitan dengan Roma dan Kekaisaran Romawi. Metode penelitian yang digunakan adalah kualitatif dengan studi hermeneutik berdasarkan pendekatan-pendekatan kritis. Hasil yang ditemukan ialah Tuhan yang berdaulat atas umat dan pemerintah. Kemudian, umat dan pemerintah memiliki hubungan mutualisme dan saling bergantung. Keduanya bekerja sama dalam tatanan kehidupan. Pemerintah adalah utusan Allah yang diberi tugas untuk melindungi dan membantu umat.Umat memberi hormat kepada pemerintah sebagai pelayan Allah.